Single cell transcriptomic analysis of murine lung development on hyperoxia-induced damage - Hurskainen, Maria; Mižíková, Ivana; Cook, David P.; Andersson, Noora; Cyr-Depauw, Chanèle; Lesage, Flore; Helle, Emmi; Renesme, Laurent; Jankov, Robert P.; Heikinheimo, Markku; Vanderhyden, Barbara C.; Thébaud, Bernard (Nature communications, 2021)
During late lung development, alveolar and microvascular development is finalized to enable sufficient gas exchange. Impaired late lung development manifests as bronchopulmonary dysplasia (BPD) in preterm infants. Single-cell RNA sequencing (scRNA-seq) allows for assessment of complex cellular dynamics during biological processes, such as development. Here, we use MULTI-seq to generate scRNA-seq profiles of over 66,000 cells from 36 mice during normal or impaired lung development secondary to hyperoxia with validation of some of the findings in lungs from BPD patients. We observe dynamic populations of cells, including several rare cell types and putative progenitors. Hyperoxia exposure, which mimics the BPD phenotype, alters the composition of all cellular compartments, particularly alveolar epithelium, stromal fibroblasts, capillary endothelium and macrophage populations. Pathway analysis and predicted dynamic cellular crosstalk suggest inflammatory signaling as the main driver of hyperoxia-induced changes. Our data provides a single-cell view of cellular changes associated with late lung development in health and disease. It is unclear how changes in gene expression are induced by changes in oxygen levels during late lung development. Here, the authors provide data from MULTI-seq scRNAseq in mice showing exposure to higher oxygen levels affects cell fates, especially for alveolarisation, and define gene/cell signatures of impaired lung development under hyperoxia.